EXISTING PROBLEMS AND DEVELOPMENT COUNTERMEASURES OF BIOLOGY TEACHING IN RURUAL MIDDLE SCHOOLS - Piaopiao Sun, Bo Peng; Chuanling Zhang, Chuanling Zhang (Top Educational Review Journal (TERJ), 2022)
At present, with the rapid development of biology, the national basic education also pays more and more attention to biology curriculum, updates the educational concept, and implements the curriculum reform, which has significantly improved the quality of biology teaching in middle school. However, due to the uneven distribution of educational resources between urban and rural areas, there is still a big gap in biology teaching between rural and urban areas. This paper mainly analyzes the main problems of biology teaching in rural middle schools through literature research and combined with the current teaching situation of several rural middle schools in Henan Province. The results show that the problems existing in biology teaching in rural middle schools mainly focus on three aspects: teachers, biology experiment teaching, and the development and utilization of biology curriculum resources. This paper aims to investigate and study the main problems existing in biology teaching in rural middle schools, and then put forward targeted development countermeasures to improve the quality of biology teaching in rural middle schools and narrow the teaching gap between urban and rural areas. Such as strengthening the construction of biology teachers and promoting teachers' professional development, changing the concept of biological experiments and strengthening the construction of laboratories, on the basis of making full use of school resources, vigorously developing natural resources, and network resources. The number of rural middle schools in China is huge and the teaching situation is complex. Therefore, this study is not comprehensive. It is the problem of most rural schools, not all schools. Rural education is the weak point of Chinese education, and biology teaching is the weak point of rural education. Analyzing the existing main problems of biology teaching in rural middle schools and putting forward development countermeasures can not only enrich the theoretical research of rural education, but also provide reference for the teaching practice of rural teachers.